Functional and brain activation changes in females with subcortical subacute stroke captured through functional near infrared spectroscopy: a case series. - Peters, Sue; Fitzgibbon-Collins, Laura K.; Luan, Siying; Kohli, Sarthak; Durand, Nathan; Teasell, Robert; Viana, Ricardo; MacDonald, Shannon L.; Bhangu, Jaspreet; Fleet, Jamie L (Physiotherapy Theory & Practice, 2026)
Background: Females have worse functional outcomes than males after a stroke including worse standing balance, slower gait speed, and higher fatigue levels. The current understanding of stroke recovery mechanisms has not yet been able to explain why females have worse outcomes compared to males. Functional Near Infrared Spectroscopy (fNIRS) amplitude offers information on the level of cognitive effort required to perform a task, as well as the impact of rehabilitation on brain function. Objectives: The aim of this case series was to use fNIRS to provide detailed prefrontal cortex activation data on several functional lower extremity sensorimotor tasks in females admitted to a stroke inpatient rehabilitation unit. Methods: Four female participants completed impairment, balance, gait, and fatigue measures as well as fNIRS assessments at admission and discharge from the inpatient stroke rehabilitation unit. fNIRS assessments included quiet and semi-tandem standing, and supine ankle sensorimotor tasks. Results: All participants had a subcortical ischemic stroke with improvements in sensorimotor impairment (average 9-point increase on the Fugl-Meyer), balance (average 29-point increase on the Berg Balance Scale), and gait (average 0.25 m/s increase in gait speed, average 30 m increased distance on the 2-minute walk test) at discharge. Larger fNIRS amplitudes were observed at baseline which were reduced at discharge for the three supine tasks, and these changes were less evident for the two standing tasks. Two females had decreased fatigue at discharge with the other two females experiencing small increases (average 0.5-point decrease on the Fatigue Severity Scale). Conclusions: For females admitted to an inpatient stroke unit, relationships may be present with improvements on clinical scores and decreased fNIRS amplitude during supine tasks, with standing tasks generating more diverse fNIRS responses. These findings suggest that fNIRS can provide prefrontal cortex activation data in females on an inpatient stroke unit and that a standard inpatient rehabilitation program appears to have an effect on fNIRS amplitudes.